2022
DOI: 10.1186/s12951-022-01506-6
|View full text |Cite
|
Sign up to set email alerts
|

Differentiated kidney tubular cell-derived extracellular vesicles enhance maturation of tubuloids

Abstract: The prevalence of end-stage kidney disease (ESKD) is rapidly increasing with the need for regenerative therapies. Adult stem cell derived kidney tubuloids have the potential to functionally mimic the adult kidney tubule, but still lack the expression of important transport proteins needed for waste removal. Here, we investigated the potential of extracellular vesicles (EVs) obtained from matured kidney tubular epithelial cells to modulate in vitro tubuloids functional maturation. We focused on organic anion tr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 63 publications
0
4
0
Order By: Relevance
“…Renal tubular epithelial cells possess a highly polarized membrane structure, with the apical membrane in direct contact with pro-urine, facilitating the excretion of EVs into urine. 25 , 53 , 54 The Apical membrane is more active in EV excretion than the basolateral membrane, with distinctive EV proteomics and miRNA profiles. Moreover, a dense monolayer of renal tubules establishes high impermeability, allowing less than 1% of EVs to pass through over 72 hours.…”
Section: Discussionmentioning
confidence: 99%
“…Renal tubular epithelial cells possess a highly polarized membrane structure, with the apical membrane in direct contact with pro-urine, facilitating the excretion of EVs into urine. 25 , 53 , 54 The Apical membrane is more active in EV excretion than the basolateral membrane, with distinctive EV proteomics and miRNA profiles. Moreover, a dense monolayer of renal tubules establishes high impermeability, allowing less than 1% of EVs to pass through over 72 hours.…”
Section: Discussionmentioning
confidence: 99%
“…This study underlines the important role of EV communication during nephrogenesis, and additional studies will be of interest to fully understand the EV mechanisms of action during kidney development. A recent study found that EVs from engineered kidney tubular epithelial cells improve tubuloid maturation [ 14 ]. Indeed, EVs from proximal tubule epithelial cells overexpressing organic anion transporter, a membrane transporter involved in the excretion of waste, enhanced tubuloid polarization, cilia structure formation and epithelial transport capacity.…”
Section: Evs In Kidney Physiology and Developmentmentioning
confidence: 99%
“…Indeed, EVs from proximal tubule epithelial cells overexpressing organic anion transporter, a membrane transporter involved in the excretion of waste, enhanced tubuloid polarization, cilia structure formation and epithelial transport capacity. Some authors also suggest that EVs can be a major tool for developing bioartificial kidneys by promoting dense cilia structures and organoid differentiation and maturation [ 14 ].…”
Section: Evs In Kidney Physiology and Developmentmentioning
confidence: 99%
“…110,111 Similarly, EVs isolated from engineered proximal tubule cells were shown to improve the functional maturation of “tubuloids” (organoids showing a predominant tubular phenotype) including enhanced transport capacity of organic anion transporter 1. 112 This raises the possibility that EVs mediate proximal-to-distal cross-talk to modify transport function (see Figure 5). 113 If confirmed in vivo , this would represent a novel layer of regulation in addition to other signaling systems.…”
Section: Evs In Tubular Function and Diseasementioning
confidence: 99%